Mitral leaflet separation index correlation with mitral stenosis severity, a reliable easy 2-d echocardiography technique - Hussain, Saba; Fateh Ali Tipoo Sultan; Mariam Naz; Sumyia Gurmani; Shazia Rasheed (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate accuracy of mitral leaflet separation index for the determination of mitral stenosis severity in patients with rheumatic mitral stenosis. Method: The prospective, cross-sectional study was conducted at the National Institute of Cardiovascular Diseases, Karachi, from March 2021 to February 2022, and comprised patients with rheumatic mitral stenosis detected on echocardiography. The best end-diastole parasternal long axis and apical four-chamber views were acquired and Mitral leaflet separation was measured as the distance between the inner edges of the tip of mitral leaflets. Pearson correlation coefficient was computed for mitral leaflet separation index and mitral valve area. Receiver operating characteristic curve was used to determine the cut-off value of the mitral leaflet separation indexto categorise mitral stenosis. Data was analysed using SPSS 19. Results: Of the 277 patients, 205(74%) were females and 72(26%) were males. The overall mean age was 39.93±11.22 years. The mean mitral leaflet separation index value was 7.65±2.23. The correlation was significant and strong between mitral leaflet separation index and mitral valve area on planimetry (p<0.001), and was significant and moderate when measured by pressure half-time (p< 0.001). Mitral leaflet separation index cut-off value <8.625mm and <8.25mmcould predict severe mitral stenosis with 84% and 86.3% sensitivity and 84.6% and 78.3% specificity on planimetry and pressure half-time, respectively. Conclusion: The mitral leaflet separation index was found to be an independent, reliable and simple measure for assessing mitral stenosis severity. Key Words: Echocardiography, Mitral stenosis, Mitral leaflet separation index, Pressure half-time, Planimetry.